2020
DOI: 10.1186/s12884-020-02910-2
|View full text |Cite
|
Sign up to set email alerts
|

“Midwives do not appreciate pregnant women who come to the maternity with torn and dirty clothing”: institutional delivery and postnatal care in Torit County, South Sudan: a mixed method study

Abstract: Background: South Sudan has one of the highest maternal mortality ratios in the world, at 789 deaths per 100,000 live births. The majority of these deaths are due to complications during labor and delivery. Institutional delivery under the care of skilled attendants is a proven, effective intervention to avert some deaths. The aim was to determine the prevalence and explore the factors that affect utilization of health facilities for routine delivery and postnatal care in Torit County, South Sudan.Methods: A c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 47 publications
4
11
0
Order By: Relevance
“…Our study also highlights the importance of completing four or more ANC visits for greater utilization of institutional delivery aswomen completing four or more ANC visits were nearly three times more likely to deliver in health facility. This nding is in-line with the ndings of studies conducted inChitwan 20 and Kavrepalanchowk 31 districts of Nepal and also in Ethiopia 32 and Sudan 33 .Other different studies 25, 34,35 ,36 also showed that improving ANC practices can help increase institutional delivery. This can be justi ed by the fact that women are women are also counseled for institutional delivery in their ANC check-up as birth-preparedness is also a component of ANC.Similarly, women having more number of children were also less likely to practice institutional delivery in our study which is in accordance with the ndings of studies in Bangladesh 37,38 , and Nepal 26 .…”
Section: Multivariate Analysissupporting
confidence: 87%
“…Our study also highlights the importance of completing four or more ANC visits for greater utilization of institutional delivery aswomen completing four or more ANC visits were nearly three times more likely to deliver in health facility. This nding is in-line with the ndings of studies conducted inChitwan 20 and Kavrepalanchowk 31 districts of Nepal and also in Ethiopia 32 and Sudan 33 .Other different studies 25, 34,35 ,36 also showed that improving ANC practices can help increase institutional delivery. This can be justi ed by the fact that women are women are also counseled for institutional delivery in their ANC check-up as birth-preparedness is also a component of ANC.Similarly, women having more number of children were also less likely to practice institutional delivery in our study which is in accordance with the ndings of studies in Bangladesh 37,38 , and Nepal 26 .…”
Section: Multivariate Analysissupporting
confidence: 87%
“…Further, the link has been shown, in many regions of the world, between perceived quality of care and families' decisions about when and where to seek obstetric and postpartum care [4][5][6][7]. A new study from Bayo et al [8], is no exception: perceived poor quality, including the threat of small or in-kind payment for services, was found to be a main driver in the incredibly low institutional delivery rates in one region in South Sudan.…”
Section: Commentmentioning
confidence: 99%
“…How can improving quality of care and client experiences be used as an 'accelerant' instead of a deterrent to care-seeking? While health care workers and policymakers often attribute low facility utilization to "traditions" and "culture," women themselves often place primacy on the perceived quality of care and will overcome barriers of gender inequity, decision-making power, cultural norms, transport, and geography to access what they perceive as high-quality care [8].…”
Section: Commentmentioning
confidence: 99%
See 1 more Smart Citation
“…This indicates the prevailing social attitudes towards people from lower socioeconomic backgrounds. Studies from different contexts have also revealed likewise (25,48).…”
Section: Discussionmentioning
confidence: 77%